2018
DOI: 10.1121/1.5068478
|View full text |Cite
|
Sign up to set email alerts
|

Dagaare [a] is not neutral to ATR harmony

Abstract: Bodomo (1997) describes Dagaare (Gur; Ghana) as having a single low vowel, [a], which is neutral to ATR harmony. This paper presents acoustic data from a study of Dagaare <a> which is inconsistent with this description. A list of sentences was elicited from five native speakers of Dagaare. Each sentence contained <a> in one of four verbal particles situated in one of four contexts: ATR _ ATR, ATR _ RTR, RTR _ ATR, and RTR _ RTR. Formants of the low vowel were measured and compared a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…The Ozburn et al (2022) study on Dàgáárè also found that the ATR+Height pair [ɪ ~ e] was poorly discriminated, at least compared to [e ~ ɛ], in keeping with the overlap in the acoustic space of that pair, and similar to our results. However, discrimination was not significantly different for [i ~ɪ] compared to either of the other two pairs.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The Ozburn et al (2022) study on Dàgáárè also found that the ATR+Height pair [ɪ ~ e] was poorly discriminated, at least compared to [e ~ ɛ], in keeping with the overlap in the acoustic space of that pair, and similar to our results. However, discrimination was not significantly different for [i ~ɪ] compared to either of the other two pairs.…”
Section: Discussionsupporting
confidence: 90%
“…A recent study (Ozburn, Giovio Canavesi, & Akinbo, 2022) examines perception of ATR distinctions in Dàgáárè, a Mabia language of Ghana, and is the only other study besides the current one to test perception with a large number of speakers (over 20) of a language with ATR contrasts. Stimuli were kV and kVkV nonce words using front vowels [i ɪ e ɛ] in an ABX task.…”
Section: Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…While previous studies (e.g. Bodomo 1997) report that Dàgáárè has nine contrastive vowels, a recent acoustic study (Ozburn et al 2018) suggests that Central Dàgáárè has a tenth vowel. The tenth vowel is reported to be /´/, which is an [ATR] (advanced tongue root) counterpart of the [RTR] (retracted tongue root) vowel /a/.…”
Section: Vowelsmentioning
confidence: 84%
“…Using Kernel density estimation, the contour plot in Figure 3 shows the distribution of the two low vowels within the vowel space based on the acoustic study by Ozburn et al (2018). The results of the research in Lloy et al (2019) also suggest that the tenth vowel is (partially) contrastive.…”
Section: Vowelsmentioning
confidence: 97%